Evidence-Informed Primary Bereavement Care: A Study Protocol of a Knowledge-to-Action Approach for Systems Change. Issue 1 (February 2015) - Lang, Ariella; Fleiszer, Andrea R.; Duhamel, Fabie; Aston, Megan; Carr, Tracy; Goodwin, Sharon
Using a systems change approach to knowledge-to-action, the purpose of this study is to increase organizational and practitioner uptake of an evidence-informed primary bereavement care guideline in home and community care through a researcher-knowledge-user partnership. Guided by the Consolidated Framework for Implementation Research, a single case study design will be used to examine system change in its natural context. The project integrates an organizational change initiative and a research study. Multiple data collection and analysis strategies will be used to explore and map the interactive synergistic process of interconnected decisions and actions. Iterative cycles of analysis and feedback will incite knowledge-user reflection and action, shape and substantiate findings, use data in a timely fashion to inform and guide next steps, and ensure ongoing monitoring and evaluation of the process.